KUALITAS PELAYANAN KARANTINA HEWAN PADA KANTOR BALAI KARANTINA PERTANIAN KELAS II PALU, WILAYAH KERJA BANDARA MUTIARA SIS AL JUFRI PALU - Suartono, Gusti Ngurah (Katalogis, 2016)
The background of this research is that Class II Agricultural Quarantine Office of Palu, Mutiara-Sis Al-Jufri Airport working area, has a tougher challenge than the other working areas. The challenges are such as supervising and serving the service users of animals quarantine who are in or out using air transport services through Mutiara Airport Sis Al Jufri Palu where the activities of loading and unloading are following the commercial flights scheduleÂ from Monday â€“ Sunday, 06:00 am â€“ 24:00 pm , while the clerk who are on service only 3 (three) people of the ideal number 10 (ten) people. This research is a qualitative descriptive research with object of research the service of Animal Quarantine at Class II Agricultural Quarantine Office of Palu, Mutiara-Sis Al-Jufri Airport working area. While the concept used is Tangibles, Reliability, Responsiveness, Assurance and Empathy which are expressed in the concept of service quality (servqual). The results of this study show that the quality of animal quarantine service at the Central Office of Agricultural Quarantine Class II Palu Work Areas Mutiara Airport Sis Al Jufri Palu general judging of the five variables in terms of both quantity and quality of the infrastructure needed in the service has been very good as well the quality of the officers who provide excellent service. But what is still lacking is the number of service personnel only 3 (three) and therefore contributes to the number of days and hours of service, which should service animal quarantine adjusted to flight schedule commercial aircraft from Monday - Saturday from 06.00 pm - 24.00 pm, but the fact now they simply could serve as civil servants working hours are from Monday - Friday from 07:30 pm - 16:00 pm.